Diurnal impact of atmospheric stability on inter-farm wake and power generation efficiency at neighboring onshore wind farms in complex terrain. (1st September 2022) - Wang, Qiang; Luo, Kun; Wu, Chunlei; Mu, Yanfei; Tan, Junyao; Fan, Jianren
Highlights: A refined wind farm parameterization was used to reflect inter-farm interaction. The inter-farm wake and power production changes show the diurnal cycles. The downwind farm power loss at night is 3 times larger than that at daytime. The largest power production losses are suffered before dawn and after dusk. The topographic effect in the stable layer outperforms in unstable conditions. Abstract: Enhancing the power production efficiency of large-scale wind farms is challenging for onshore wind power due to the variability of atmospheric conditions. This work aims to study the impact of atmospheric stability on the inter-farm wake pattern, topographic effect, and power production changes at two neighboring wind farms in Hami City, Xinjiang of China over complex terrain. The results show a discernible diurnal cycle property. At night in a stable layer with hindered mixing, the inter-farm wake persists around 20 km downstream, and the greatest relative wind deficit increases by 8%. However, during the daytime unstable layer with elevated turbulence, shows a limited deficit and recovers about 6 km downstream. Accordingly, a mean relative power production reduction of 17% is subjected to the downwind farm at night, about a factor of 3 greater than that at daytime, when the mean value is only 6%. Interestingly, the largest power production losses are experienced with a larger range between maximum and minimum before dawn and after dusk due to the notable inter-farm wake with a streaky structure related to the large coherent buoyant caused by the tendency of heat flux over the complex terrain. Moreover, the topographic speed-up in the stable layer outperforms that in unstable conditions.